Auditor Integration of IT Specialist Input on Internal Control Issues: How a Weaker Team Identity Can Be Beneficial - Estep, Cassandra (The Accounting Review, 2021)
ABSTRACT I investigate how auditors integrate information technology (IT) specialist input into internal control over financial reporting (ICFR) issue classifications. Given the ill-structured nature of evaluating ICFR issues and the impact of these issues on audit quality, combining knowledge from different perspectives is likely beneficial. Drawing on social identity theory, I predict and find that a weaker one-team identity between auditors and IT specialists yields benefits. Auditors with a weaker versus stronger team identity place more weight on IT specialist input for IT-related issues and differentially weight higher and lower quality input for non-IT issues. I also find that more severe ICFR issues drive the predicted results. My study provides insight into how team identity influences auditor integration of input from specialists. The implications of my study are of interest to researchers, regulators, and practitioners, especially as recent firm initiatives encourage a one-team view for auditors and IT specialists.